Bluish-gray fingernail discoloration due to the use of nivolumab. (March 2021) - Ocampo, Miguel Michel; Lerner, Jaren; Dasanu, Constantin A
Introduction: Immune checkpoint inhibitors have improved clinical outcomes in a wide range of cancers. While skin toxicity is not uncommon with immune checkpoint inhibitors, generalized nail discoloration has not been reported with their use in oncology. Case report: Herein, we report a unique case of bluish-gray fingernail discoloration due to nivolumab therapy for relapsed melanoma. Management and outcome: This condition reversed completely 10 weeks after nivolumab discontinuation. Naranjo nomogram assessment renders the causality relationship between nivolumab and nail discoloration probable. Discussion: To our knowledge, this is the first case report of an unusual bluish-gray nail discoloration due to therapy with nivolumab. The mechanism by which nivolumab causes this side effect remains to be elucidated.